Decision Making in Financial Behavior: A Systematic Literature Review¬ - Havidotinnisa, Siti; Puspasari, Dewi; Purnomo , Budi Supriatono; Purnamasari, Imas (Westscience Press, 2024)
Digitalization is a major factor in the rapid dissemination of information, especially in the financial world. This has an impact on the emergence of various financial behaviors that can affect Investor Decision Making in investing. Financial behavior is a key factor that can affect the quality of Investor Decision Making, which is characterized by achieving optimal results and avoiding biased decisions. Effective financial behaviors are very important and should not be taken lightly. As an investor, adopting appropriate financial behaviors is key to overcoming behavioral biases associated with Investor Decision Making. The purpose of this study is to investigate the current state of behavioral finance research with a focus on the significant factors that influence Investor Decision Making. Driven by the need to create a comprehensive literature on peer pressure, this study used a bibliometric approach by identifying 92 studies using the term